Quality of transitional care of children with chronic diseases: a cross-sectional study - Caroline Cechinel-Peiter; Gabriela Marcellino de Melo Lanzoni; Ana Lúcia Schaefer Ferreira de Mello; Aline Marques Acosta; Juliana Coelho Pina; Selma Regina de Andrade; Nelly Donszelmann Oelke; José Luís Guedes dos Santos (SciELO, 2022)
Abstract Objective: To analyze which factors may be associated with the quality-of-care transition of children with chronic diseases from the hospital to their home. Method: A cross-sectional, quantitative study, carried out in two hospitals in Southern Brazil, from February to September 2019. Participants included 167 family members of children with chronic disease. Data collection took place through a demographic questionnaire, and the use of the Brazilian version of the Care Transitions Measure (CTM-15). Results: The average score for the quality of care transition was 90.1 (sd = 19.5) (0-100). Factor 1, "Health management preparation", was the one with the highest self-perceived average, 92.3 (sd = 11.6), while Factor 4, "Care plan", had the lowest average, 86.3 (sd = 21.3). The quality of care transition was higher for patients living in municipalities belonging to health regions other than the hospital's. Conclusion: The quality of care transition for children with chronic diseases, perceived by the children's family members, in the discharge process from the hospital to home, was considered high. Living in a health region other than the hospital's region was associated with better perception of the quality of care transition.